2022
DOI: 10.3390/agriculture12122153
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Screening of the Foliage of Eucalyptus Species Harvested in Different Seasons for Modulating Rumen Fermentation and Methane Production

Abstract: The aim of this study was to assess the effects of five eucalyptus species (Eucalyptus camaldulensis, E. leucoxylon, E. astringens, E. sideroxylon, and E. lehmannii), harvested in spring, autumn, or winter from two Tunisian arboretums, on in vitro rumen fermentation and methanogenesis. Batch cultures were performed to determine rumen fermentation kinetics and end-product formation after 24 h of incubation. The foliage of the species E. sideroxylon and E. lehmannii showed the greatest digestibility coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Leaves from the spring harvest showed higher concentrations of OM, lipids, NDF, ADF, and ADL (Table 1). Other studies carried out in the literature [17,32] pointed out the significant effect of the harvest time on the nutrient concentrations of plants. The environmental conditions and maturation state are the main factors that influence the chemical composition of plants [33,34].…”
Section: Chemical Composition and Secondary Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaves from the spring harvest showed higher concentrations of OM, lipids, NDF, ADF, and ADL (Table 1). Other studies carried out in the literature [17,32] pointed out the significant effect of the harvest time on the nutrient concentrations of plants. The environmental conditions and maturation state are the main factors that influence the chemical composition of plants [33,34].…”
Section: Chemical Composition and Secondary Metabolitesmentioning
confidence: 99%
“…Different ruminant species have different comparative abilities to digest feeds; therefore, examining the fermentative capacity of the same feed with microbial populations from sheep and goats is important. Furthermore, the harvesting season dramatically affects the nutritive value of plants [17]. Horst et al [17] observed that the digestibility and the acetate-to-propionate ratio of eucalyptus foliage were higher during the winter than during autumn and spring without affecting methane emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation